307 Stereotactic Radiosurgery for Pediatric Intracranial Ependymomas: An International Multicenter Study. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Kano, Hideyuki; Su, Yan-Hua; Wu, Hsiu-Mei; Simonova, Gabriela; Liscak, Roman; Cohen-Inbar, Or; Sheehan, Jason P; Meola, Antonio; Sharma, Mayur; Barnett, Gene H; Mathieu, David; Vasas, Lucas T; et al.
Abstract: INTRODUCTION: Stereotactic radiosurgery (SRS) is a potentially important option for pediatric patients with intracranial ependymoma. We analyzed the outcomes of intracranial ependymoma patients who underwent SRS as a part of multimodality management. METHODS: Seven participating centers of the International Gamma Knife Research Foundation (IGKRF) identified 47 patients who underwent SRS for 57 intracranial ependymomas. The median patient age was 8 yr (range: 2.9-17.2). All patients had previous surgical resection followed by fractionated radiation therapy. Twenty-one patients had low-grade (grade 2) ependymomas (29 tumors) and 26 patients had high-grade (grade 3) ependymomas (28 tumors). The median radiosurgery target volume was 1.6 cc (range: 0.03-15.3 cc), and the median margin dose was 15 Gy (range: 9-24 Gy). RESULTS: At a median follow-up of 22 mo after SRS (range: 4.5-220 mo), 26 (55%) patients were alive and 21 (45%) patients died. The overall survival after SRS was 89% at 1 yr, 47% at 3 yr, and 39% at 5 yr. Smaller tumor volume was significantly associated with longer patient survival ( P = .015) while tumor grade was not associated with patient survival. Fourteen patients (grade 2: N = 5, grade 3: N = 9) developed new untreated tumors in the spinal or cranial neuraxis. The rate of developing distant tumor relapse after SRS was 19% at 1 yr, 44% at 3 yr, and 44% at 5 yr. Supratentorial tumor location was significantly associated with higher rate of developing distant tumor relapse after SRS ( P = .034). The progression-free survival after SRS was 64% at 1 yr, 58% at 2 yr, 41% at 3 yr, and 29% at 5 yr. There were no factors associated with progression free survival. Symptomatic adverse radiation effects developed in 2 patients (4%). CONCLUSION: SRS provides another management option for pediatric patients with intracranial ependymomas who have failed surgery and radiation therapy.